Assessment of anesthetic gases in a central hospital. Issue 4 (17th July 2020) - Norton, Pedro; Pinho, Paulo; Xará, Daniela; Pina, Fátima; Norton, Maria
Abstract: Introduction: Adverse health effects related with chronic exposure to waste anesthetic gases remain controversial. Strict threshold values are recommended to minimize possible health risks. The objective of our study was to measure the concentration of waste anesthetic gases in different hospital settings in an 11-year period. Materials and methods: Six-monthly assessment of nitrous oxide, sevoflurane, and desflurane was made between 2005 and 2016 in different hospital departments. Trace gas analysis was performed by infrared spectroscopy. Results: An anesthetic gas concentration above the upper limit of the threshold value was found in computed tomography/magnetic resonance imaging (CT/MRI) (45.5%), ambulatory operating room (34.5%), and in the burn unit (31.6%). Desflurane assessment was more frequently above the upper limit of threshold value (12.37%). Discussion: In the CT/MRI department, the small number of air cycling per hour and the frequent use of a face mask with the associated risk of leakage may explain the results. In burn unit patients inhalatory route is also frequent. Desflurane is widely used for its rapid elimination and rapid recovery, which is compatible with the results. Being odorless, it may be connected to undetected escape. Conclusion: The places with more anesthetic agents exposure were the CT/MRI, the ambulatory operating room, and the burn unit. Desflurane was the anesthetic agent more frequently above the upper limit of threshold value. To complement environmental surveillance, it is essential to establish a health surveillance system for professionals exposed to anesthetic agents.